Characterisation of germline mutations in the neurofibromatosis type 1 (NF1) gene. Issue 9 (September 1995) - Upadhyaya, M; Maynard, J; Osborn, M; Huson, S M; Ponder, M; Ponder, B A; Harper, P S
Abstract : Neurofibromatosis type 1 is one of the most common inherited disorders with an incidence of 1 in 3000. The search for NF1 mutations has been hampered by the overall size of the gene, the large number of exons, and the high mutation rate. To date, fewer than 90 mutations have been reported to the NF1 mutation analysis consortium and the details on 76 mutations have been published. We have identified five new mutations using single strand conformation polymorphism (SSCP) and heteroduplex analysis (HA) and three intragenic deletions with the microsatellite markers. Of the five new mutations, two were in exon 27a, two in exon 45, and one in exon 49 and these include 4630delA, 4572delC, R7846X, T7828A, and one in the 3' untranslated region (3' UTR). The two nucleotide alterations in exon 27a and the one in exon 45 are predicted to produce a truncated protein.